Pemberdayaan remaja desa candirejo melalui pkbm untuk meningkatkan skill bersosialisasi di masyarakat - Azzahra, Shafanafi (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2024)
Youth empowerment is an effort to build the activeness of adolescents so that one day they can become people who can maximize their potential they bring benefits to the surrounding environment. Youth empowerment must be built so that these adolescents can grow and develop into productive individuals. In PKBM Candirejo, adolescents who have been active as TBM (Taman Belajar Masyarakat) managers are 11 people, consisting of 3 men and 8 women. This research was conducted in Candirejo Village, Semarang, Central Java in September 2021 using descriptive qualitative methods and data obtained from interviews with PKBM managers and village youth who manage TBM services. This study concluded that the empowerment of village youth has a very good impact on building character, skills, knowledge, and social skills that are beneficial for their future.